Roles of Atomizing Gas in Swirl Effervescent Atomization - H. A. Hamid, Ahmad; A. Ghaffar, Zulkifli; C. Rus, Nurulhanis (International Journal of Engineering and Technology, 2018)
Issues of propellant atomizing, mixing and viscous loss become increasingly more important as the thrust chamber are reduced in size. The present investigation examines the behavior of resulting sprays emanating from swirl effervescent atomizers at various gas-to-liquid ratios (GLRs) and aeration tube configurations. A series of cold flow test has been conducted, where water and nitrogen were used as simulation fluids. Results show that the injection of atomizing gas tends to reduce the spray angle and the discharge coefficient. Results also indicate narrower spray angle and lower discharge coefficient at higher GLRs. A smaller total aeration hole size also leads to a narrower spray angle and a higher pressure drop for the gas injection. Interestingly, a smaller total aeration hole size produces higher discharge coefficient. In general, the atomizing gas has shown to significantly alter the resulting sprays of a swirl effervescent atomizer even at a relatively low GLR.Â